Culture-confirmed chlamydia pneumoniae infection - Bahnu, S.; Ngeow, Yun Fong; Wong, W.K. (Faculty of Medicine, University of Malaya, 1996)
A strain of Chlamydia pneumoniae was isolated from the throat swab of a 45 year-old female patient with tracheobronchitis who responded well to doxycycline therapy. The isolate was confirmed by fluorescent antibody staining and by polymerase chain reaction. As there are no distinct clinical features to indicate C pneumoniae respiratory infections, laboratory confirmation is required for definitive diagnosis.